Eastern dobsonfly (adult), hellgrammite (larva) Corydalus cornutus (Linnaeus) (Insecta: Megaloptera: Corydalidae: Corydalinae) - Donald W. Hall (EDIS)
The eastern dobsonfly is one of our largest non-lepidopteran insects. Its larvae, known as hellgrammites, are the top invertebrate predators in rocky streams where they occur. Adult male dobsonflies are particularly spectacular because of their large sickle-shaped mandibles (jaws). This 4-page fact sheet was written by Donald W. Hall and published by the UF Department of Entomology and Nematology, April 2013.